Complements or substitutes? Preferential and multilateral trade liberalization at the sectoral level - Antoni Estevadeordal; Christian Volpe Martincus; Mitsuyo Ando (Inter-American Development Bank (IDB), 2009)
This paper explores the relationship between preferential and multilateral trade liberalization at the sectoral level using a unique dataset that includes data on most favored nation (MFN) and bilateral preferential tariffs at the 4-digit ISIC level for 11 Latin American countries over the period 1985-2005. We find evidence of heterogeneity across sectors. While in some industries, complementary effects between both kinds of trade liberalization are observed, in others no significant links are detected and-in a few cases-even substitutability seems to prevail. Variation across sectors appears to be systematically related to both import demand elasticities and countries' sectoral comparative advantages.
hdl:11319/2550
Keywords: F13; F14; C20; 330; Trade Liberalization; Regionalism; Latin America